Answer:
Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
We have
[tex]h(7)=-29\to x=7,\ y=-29\\\\h(-4)=26\to x=-4,\ y=26[/tex]
Substitute to the formula of a slope:
[tex]m=\dfrac{26-(-29)}{-4-7}=\dfrac{55}{-11}=-5[/tex]
Put m = -5, x = 7 and y = -29 ot the equation of a line:
[tex]-29=(-5)(7)+b[/tex]
[tex]-29=-35+b[/tex] add 35 to both sides
[tex]6=b\to b=6[/tex]
Finally
[tex]y=-5x+6[/tex]
h(6) → put x = 6 to the equation of a line:
[tex]h(6)=-5(6)+6=-30+6=-24[/tex]